2019
DOI: 10.1088/1741-2552/ab39ce
|View full text |Cite
|
Sign up to set email alerts
|

Predicting individual decision-making responses based on the functional connectivity of resting-state EEG

Abstract: Objective. Despite increasing evidence revealing the relationship between task-related brain activity and decision-making, the association between resting-state functional connectivity and decision-making remains unknown. Approach. In this study, we investigated the potential relationship between the network revealed in the resting-state electroencephalogram (EEG) and decision responses and further predicted individuals’ acceptance rates during the ultimatum game (UG) based on the functional connectivity revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 74 publications
1
36
0
Order By: Relevance
“…The human brain is a complex network comprising a large number of interconnected brain regions, and neural impulses are always transmitted and integrated across the spatially separated (but functionally connected) brain regions [44]. Many studies have revealed that the resting‐state brain network is closely related to human behavior and disease progression [45 48]. Accordingly, the organizational structure of the resting‐state brain network may play an important role in SMR modulation.…”
Section: Causes Of Mi‐bci Inefficiencymentioning
confidence: 99%
“…The human brain is a complex network comprising a large number of interconnected brain regions, and neural impulses are always transmitted and integrated across the spatially separated (but functionally connected) brain regions [44]. Many studies have revealed that the resting‐state brain network is closely related to human behavior and disease progression [45 48]. Accordingly, the organizational structure of the resting‐state brain network may play an important role in SMR modulation.…”
Section: Causes Of Mi‐bci Inefficiencymentioning
confidence: 99%
“…Figure 4 further displays the atypical interactions underlying the task information processing for ADHD in which long-range connectivity between the frontal and occipital lobes could be found. In fact, during the visual task, the occipital lobe is responsible for receiving and integrating visual information, which was revealed by Li et al's study on constructing large-scale cortical networks for P3 [ 59 ], while the frontal lobe contributes to a wide range of cognitive functions, such as attention [ 60 ], decision-making [ 61 ], and executive control [ 62 ]. The frequency-specified synchronization between these regions can effectively modulate cognitive information processing [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Last, in this study, candidate EEG predictors were restricted only to the EEG band powers. If more EEG electrodes are available, EEG network measures can also be used to predict the dynamic ranges of EEG features [42,43], which we would like to pursue in our future study.…”
Section: Discussionmentioning
confidence: 99%